2011
DOI: 10.1002/ijc.25953
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged expression of the γ‐H2AX DNA repair biomarker correlates with excess acute and chronic toxicity from radiotherapy treatment

Abstract: The normal tissue tolerance levels to fractionated radiotherapy have been appreciated by a century of careful clinical observations and radiobiological studies in animals. During clinical fractionated radiotherapy, these normal tissue tolerance levels are respected, and severe sequelae of radiotherapy are avoided in the majority of patients. Notwithstanding, a minority of patients experience unexpectedly severe normal tissue reactions. The ability to predict which patients might form this minority would be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 23 publications
4
96
1
Order By: Relevance
“…Radiotherapy is one of the major therapeutic strategies for cancer treatment and results in DNA damage, including DSBs, which in turn initiates a variety of signaling events in cancer cells (19). DSBs lead to the phosphorylation of H2AX, and we and others have used this as a marker for the cellular response to radiation-induced DNA damage (20)(21)(22). Our results showed that the combined treatment of sorafenib and radiation delayed the clearance of γH2AX, suggesting that sorafenib prevents DNA repair and hence increases radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is one of the major therapeutic strategies for cancer treatment and results in DNA damage, including DSBs, which in turn initiates a variety of signaling events in cancer cells (19). DSBs lead to the phosphorylation of H2AX, and we and others have used this as a marker for the cellular response to radiation-induced DNA damage (20)(21)(22). Our results showed that the combined treatment of sorafenib and radiation delayed the clearance of γH2AX, suggesting that sorafenib prevents DNA repair and hence increases radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Transfected cells were exposed to 2 Gy X-rays, an appropriate dose according to most radical radiotherapy protocols (11). The cells were collected and stained with anti-γ-H2AX (Cell Signaling Technology) antibody at different times as previously described (12).…”
Section: Clonogenic Cell Survival In Vitromentioning
confidence: 99%
“…As a result, Naph caused the activation of cleaved caspase-3 and subsequently the cleavage of PARP in AGS cells in a dose-dependent manner. Expression of γ-H2AX, which promotes DNA repair and maintains genomic stability (15), was also induced by Naph, but the expression of Bax and Bcl-xL was not altered by Naph. These results indicated that Naph may induce apoptosis in AGS cells.…”
Section: Effect Of Naphthazarin On Ags Gastric Cancer Cell Viability mentioning
confidence: 98%